The Relationship of Knowledge, Attitude, and Behavior With Housewives' Participation in the Diski Mandiri Deli Serdang Waste Bank - Restu Auliani; Julietta Br Girsang; Desy Ari Apsari (Syntax Idea)
Community-based waste management innovation can be done through a waste bank which is the development of the 3R concept (reuse, reduce, recycle). Community participation, especially housewives, being customers of the waste bank is highly expected in supporting waste management towards a healthy, clean life while at the same time increasing economic value. This study aims to determine the relationship between knowledge, attitudes, and actions of housewives with participation in the waste bank. It is important to know and conduct an in-depth discussion so that the results obtained can be used as the basis for developing waste banks, as well as evaluating existing waste banks in the community. The type of research used is observational analytic with a case control research design with a sample size of 76 respondents (38 respondents are waste bank customers, and 38 respondents are non-waste bank customers). Data analysis using chi square test with 95% confidence level.. The results showed that there was a relationship between knowledge (p value 0.004) and the participation of housewives in the waste bank. There is a relationship between attitudes (p value 0.000) with the participation of housewives in the waste bank. There is an action relationship (p value 0.001) with the participation of housewives in the waste bank. Knowledge, attitudes and actions of waste bank customers are better than those of housewives who are not waste bank customers. Increased knowledge of attitudes and actions can be carried out in the form of socialization, counseling and community empowerment, as well as improving facilities and infrastructure in waste management can increase the participation of housewives in the waste bank. Waste banks are expected to have an impact on housewives in increasing economic value, while maintaining environmental sustainability and cleanliness.